2016
DOI: 10.4067/s0718-34292016000100006
|View full text |Cite
|
Sign up to set email alerts
|

Suplementos orgánicos para el cultivo in vitro del híbrido Laeliocattleya (Orchidaceae)

Abstract: RESUMENEl desarrollo de técnicas de micropropagación en orquídeas ofrece múltiples ventajas como la reproducción de genotipos superiores, raros, estériles o libres de enfermedades. El objetivo del presente trabajo fue evaluar el uso de suplementos orgánicos (agua de coco y pulpa de banana) en el crecimiento y desarrollo in vitro de plántulas del híbrido intergenérico Laeliocattleya (Hadrolaelia purpurata x Cattleya intermedia), comparando su respuesta con fitorreguladores de auxinas y citoquininas. Para ello s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 15 publications
(18 reference statements)
0
2
0
1
Order By: Relevance
“…The question remains whether the presence of banana pulp as a natural additive could produce similar or better effects to the auxins (IBA or ANA) in roots number and length than the components of medium (Menezes Gonçalves et al, 2016). Bananas are a good source of K, Mg, Cu and Mn, generally contain more carotenoid type lutein than provitamin A pigments, β-carotene and α-carotene and low amounts of vitamin C or A (Wall, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The question remains whether the presence of banana pulp as a natural additive could produce similar or better effects to the auxins (IBA or ANA) in roots number and length than the components of medium (Menezes Gonçalves et al, 2016). Bananas are a good source of K, Mg, Cu and Mn, generally contain more carotenoid type lutein than provitamin A pigments, β-carotene and α-carotene and low amounts of vitamin C or A (Wall, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…The addition of organic supplements to the culture media improves the development and lower production costs of orchids (Moreno and Menchaca, 2007;Pakum et al, 2016;Salazar and Vega, 2017). In general, it has been reported that adding banana to the growing media improves the development of the plant and the roots (Azlan et al, 2016;Menezes et al, 2016;Wida and Hariyanto, 2019). It has been reported that banana pulp contains natural cytokinins, mineral, carbohydrate, amino acids, niacin, vitamins, fatty acids, cellulose, sterols and polyols, which are useful for the development of plantlets (Tamura, 1970;Arditti, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Los sustratos naturales favorecen la organogénesis a su vez contribuyen con la disminución de costos en el proceso de propagación in vitro (Velázquez-Kú et al, 2016). Además, se ha demostrado que los sustratos orgánicos como la piña, el plátano y el agua de coco, promueven la morfogénesis y rizogénesis dado que producen efectos similares al de las auxinas y citocininas (Menezes et al, 2016).…”
unclassified